2009
DOI: 10.1007/s10508-009-9508-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Psychiatric Vulnerability: A Twin Study of Neuroticism and Psychoticism

Abstract: Recent evidence indicates that homosexuals and bisexuals are, on average, at greater risk for psychiatric problems than heterosexuals. It is assumed with some supporting evidence that prejudice often experienced by nonheterosexuals makes them more vulnerable to psychiatric disorder, but there has been no investigation of alternative explanations. Here we used Eysenck's Neuroticism and Psychoticism scales as markers for psychiatric vulnerability and compared heterosexuals with nonheterosexuals in a community-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 69 publications
5
29
0
Order By: Relevance
“…One Australian study consisting of nearly 3,000 twin pairs did not find the FBO effect (Zietsch et al, 2011). Other studies have also reported either an excess or a decrease in other classes of siblings among gay men so the lack of a consistent FBO effect is not unprecedented (King et al, 2005; see also Frisch & Hviid, 2006;Kangassalo et al, 2011;Zucker et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One Australian study consisting of nearly 3,000 twin pairs did not find the FBO effect (Zietsch et al, 2011). Other studies have also reported either an excess or a decrease in other classes of siblings among gay men so the lack of a consistent FBO effect is not unprecedented (King et al, 2005; see also Frisch & Hviid, 2006;Kangassalo et al, 2011;Zucker et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Blanchard (2007) has argued that samesex marriage is not a good proxy for homosexuality, and noted that the Frisch and Hviid (2006) data set included a sex ratio of more older brothers than the general population. There are two other non-replications of FBO in large samples: one twin sample from Australia (Zietsch, Verweij, Bailey, Wright, & Martin, 2011) and one nationally representative sample from the U.K. usingtruncateddata (Bogaert, 2010).In some studies where there was an association between sexual orientation and sisters, the stopping rule was found to have been contaminating the sample (Blanchard & Lippa, 2007;Zucker et al, 2007). The stopping rule is a tendency for parents to prefer to have one offspring of each sex or a preference for a particular sex and to continue to have children until they have children of the desired sexes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if shared genetic factors increase risk of mental illness and same-sex sexuality, this might create an association between our instruments and same-sex sexuality (Zietsch, Verweij, Bailey, Wright, & Martin, 2011). Finally, for instruments to produce consistent estimates, they must not affect sexual orientation other than through maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a sufficient portion of newer neuroscience literature continues to present a biologically deterministic attribution to various studies’ frequently molecular-level results (Balthazart, 2011; Savic, Garcia-Falgueras, & Swaab, 2010). As has historically been the case in many areas of science, the ‘danger’ is mostly in the interpretation, but determinism can also underlie and undermine research hypotheses (Zietsch, Verweij, Bailey, Wright, & Martin, 2011). When new research findings about intracellular molecular events or anatomical sex differences in brain ultrastructure, for example, are discussed with regard to their potential influence on sexual orientation, there is, at best, only brief speculation of possible interactions with experience, for example, a single paragraph tip of the hat to experience in Cooke, Stokas and Woolley (2007).…”
Section: The Road To Misinformed Public Policy Based On Misinterpretementioning
confidence: 99%